Legal Review of Peace Agreements on the Division of Joint Property in Marriage (Civil Law and Islamic Law Perspectives) - Gunabila Bin'Arya Dwitatama; Mahdaniyal Hasanah Nuriyyatiningrum (Jurnal Daulat Hukum, 2025)
This study analyzes the legality of amicable settlement (dading) in the division of joint marital property in natura after execution seizure, viewed from civil law and Islamic law. The objective is to determine its legal validity, implications, and conformity with the principle of substantive justice. Using a normative juridical method with statutory, conceptual, and case approaches, the study examines the Civil Code, HIR, KHI, and court decisions such as Supreme Court Decision No. 732 K/Ag/2021. Findings show that post-seizure settlements are valid and binding, fulfilling contract elements under Article 1320 of the Civil Code and consistent with the ṣulḥ principle in Islamic law, emphasizing tarāḍī (consent) and al-‘adl (justice). The integration of both systems demonstrates a balance between legal certainty and public welfare, reinforcing restorative justice in family law disputes.